Medicinal plants used by rural communities in the arid zone of Viesca and Parras Coahuila in northeast Mexico - Cristian Torres-León; Fernanda Rebolledo Ramírez; Jorge A. Aguirre-Joya; Agustina Ramírez-Moreno; Mónica L. Chávez-González; David R. Aguillón-Gutierrez; Luis Camacho-Guerra; Nathiely Ramírez-Guzmán; Salvador Hernández Vélez; Cristóbal N. Aguilar (Elsevier, 2023)
This study is the first record of medicinal plants in the southwest of the Coahuila state, an arid zone where extreme dry conditions prevail. One hundred twenty-two residents (in sixteen communities) were interviewed. The residents were questioned with a questionnaire-guided ethnomedical survey protocol about the various plants used. Seventy-seven species of medicinal plants belonging to 36 botanical families were cited. The highest use-value (UV) was calculated for Lippia graveolens Kunth (0.30); Aloe vera (L.) Burm.f. (0.20); Eucalyptus abdita Brooker & Hopper, Chamaemelum nobile (L.) All. (0.16); Mentha spicata L. (0.15) and Salvia officinalis L. (0.10). Informant consensus factor (ICF) about usages of medicinal plants ranges from 0.41 to 0.80; the highest level of agreement was determined between the informants and Respiratory System Diseases (0.80). The highest fidelity level (FL) values (100%) were identified in Flourensia cernua DC., Artisia ludoviciana Nutt., and Parthenium incanum Kunth to Gastro-intestinal System Diseases; Eucalyptus abdita Brooker & Hopper, Bougainvillea berberidifolia Heimerl, and Lippia graveolens Kunth to Respiratory System Diseases (RSD) and Cyclolepis genistoides D.Don and Ephedra antisyphilitica Berland. ex C.A.Mey. to Obstetrics, Gynecology and Urinary tract Diseases. These last two medicinal plant species ("palo azul" and "pitoreal") used by the rural communities in Viesca in the treatment of urinary tract infections and kidney stones have not been reported previously. These findings can provide new research directions for further phytochemical studies. The present study revealed that the residents are rich in ethno-medicinal knowledge and actively use medicinal plants to treat various diseases. New phytochemical and pharmacological research are needed to confirm the therapeutic potential and safety of the identified plants.